Peripheral nerve injuries attributable to sport and recreation - Toth, C. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Many different sports and recreational activities are associated with injuries to the peripheral nervous system (PNS). Although some of those injuries are specific to an individual sport, other peripheral nerve injuries occur ubiquitously within many sporting activities. This review of sport-specific PNS injuries should assist in the understanding of morbidity associated with particular sporting activities, professional or amateur. Proper recognition of these syndromes can prevent unnecessary diagnostic testing and delays in proper diagnosis. The sports most commonly associated with peripheral nerve injuries are likely football, hockey, and baseball, but many other sports have unique associations with peripheral nerve injury. This article should be of assistance for the neurologist, neurosurgeon, orthopedic surgeon, physiatrist, sports medicine doctor, and general physician in contact with athletes at risk for neurologic injuries.